How Port Service is Important for Logistic Companies? Examining Role of Service Ambidexterity and Service Agility - Rohmah, Nur (Management Analysis Journal, 2022)
Business dynamics and development demand that one of the infrastructures in shipping goods by sea, namely the Port, can improve the quality of its services. Improving service quality can be done by establishing ambidexterity services and agility services. This research elaborates on the effect of ambidexterity and agility services on customer satisfaction through port service performance. The sample used is 183 service users companies engaged in logistics; therefore, this study analyzes the business-to-business (B2B) relationship. The novelty of this study is to analyze the variables regarding port services to determine their effect on service user satisfaction. The study's results found that service ambidexterity positively affected performance and satisfaction. The research also proved that service agility affected performance and satisfaction. The study found that performance partially mediated service ambidexterity and service agility on service user satisfaction.